Conformity between learning objectives, learning activities, and assessment in Indonesian genre-text-based approach textbook - Khoirussulfa, Sajjida; Dewi Saraswati , Girindra Putri (ELT Forum: Journal of English Language Teaching, 2025)
The study aims to assess conformity between learning objectives. learning activities, and assessments in English for Nusantara Kelas VIII Textbook published by the Ministry of Education, Culture, Research, and Technology in 2022 as part of Kurikulum Merdeka. The ground theory used in the analysis of the textbook are constructive alignment by Biggs and Bloom’s taxonomy. This study uses a qualitative content analysis. This study investigates the learning objectives of reading skill in the textbook, connected with the learning activities, and how well the assessment measures it. The findings reveal that most of the reading activities showed strong alignment with the stated learning objectives and assessment tasks. The learning activities are well-designed and aligned with the alignment elements, Bloom’s action verbs, and the curriculum’s genre-based competences. However, the misalignment was noted, such as that the instructions of learning activities with the learning objectives stated. This study highlights the importance of the proper textbook design, curriculum literacy, and teacher instruction to guarantee more effective language instruction. This study supports the use of Constructive Alignment theory and action verbs of Bloom’s taxonomy in English Language Education. This study contributes to expanding the literature of research that supports outcome-based learning. This study shows the developments in aligning English textbook material in Indonesia.